Healthcare Financing for Bone Marrow Transplants: A Scoping Review - Damai Santosa; Chriswardani Suryawati; Ayun Sriatmi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Bone marrow transplantation (BMT) is a life-saving procedure for haematological malignancies and other severe blood disorders. It is need resource-intensive treatment with significant financial implications. The cost of BMT varies across different countries and healthcare systems, influenced by factors such as treatment protocols, hospital infrastructure, medication expenses, and post-transplant care. Understanding the financial aspects of BMT is crucial for improving accessibility and ensuring sustainable healthcare service. Objective to analyse the cost of BMT across different regions, identify sources of financing, and explore financial challenges and potential solutions for patients undergoing BMT. A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science databases from 2001 - 2025. MeSH Terms using ((haematology malignancy OR leukaemia OR acute leukaemia OR acute myeloid leukaemia OR acute lymphoblastic leukaemia OR myeloma OR lymphoma OR thalassemia) AND (bone marrow transplantation OR stem cell transplantation OR haematopoetic stem cell transplantation OR hematopoietic stem cell transplantation OR allogeneic transplantation ) AND (OR costing OR payer)). Data were extracted on total BMT costs, cost components, sources of financing, and financial challenges associated with the procedure. The analysis followed the Cochrane Handbook for Systematic Reviews of Interventions. Out of 528 initially screened studies, 19 articles met the inclusion criteria. The cost of BMT varied significantly by country, with developed nations reporting higher costs than developing countries. The primary cost components included hospital and treatment expenses, medications, and follow-up care. Financing sources varied across regions, including private health insurance, government-funded healthcare programs, non-profit organisations, fundraising efforts, and out-of-pocket payments. Many patients in low- and middle-income countries face financial barriers due to limited insurance coverage and high out-of-pocket expenses. BMT remains a costly procedure with significant financial challenges, particularly in regions with limited healthcare funding.